PENGGUNAAN MODEL DISCOVERY LEARNING TERHADAP PENINGKATKAN KEMAMPUAN KONEKSI DAN KOMUNIKASI MATEMATIK - Dedi Presli Halawa; Derman Buulolo; Magdalena Susanti Telaumbanua; Hardi Tambunan; Firman Pangaribuan (Ndrumi : Jurnal Ilmu Pendidikan dan Humaniora, 2023)
This study aims to determine the better improvement of students' mathematical connection and communication abilities between those participating in learning with the Discovery Learning model and those participating in direct learning, as well as to find out the differences in increasing the mathematical connection and communication abilities of students in high, medium and low groups who take learning with Discovery Learning models. Data analysis used a two-mean difference test to determine better improvement between the experimental class and the control class and one-way ANOVA with the Scheffe test to determine better improvement between the high, medium and low groups. Based on the results of the study, it can be concluded that the increase in the mathematical connection and communication skills of students who take part in learning with the Discovery Learning model is better than students who take part in direct learning. The improvement of students' mathematical connection and communication skills in the middle group was better than the high and low groups who took part in learning using the Discovery Learning model